1997
DOI: 10.1103/physrevb.55.1895
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of oxygenated (100) diamond surfaces in the presence of hydrogen

Abstract: Quantum ab initio calculations and quantum semiempirical molecular-dynamics simulations were employed to study reconstructions of ͑100͒ diamond surfaces in the presence of hydrogen and oxygen. The results indicate that the energetically most favorable structures of oxygenated surfaces are those with chemisorbed hydroxyl groups. It was found that hydrogen bonds are formed among chemisorbed oxygenated species. The formation of these hydrogen bonds lowers the adlayer energy. A number of important vibrational mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 30 publications
(23 reference statements)
3
17
1
Order By: Relevance
“…The fact that the total energy of the TS is lower than that of the reactant is true of the dissociative adsorption of a NH 3 molecule on a Si-Si dimer. 15 The vibrational frequency of the adsorbed ϪOH fragment was calculated, and the computed values 1135 and 1110 cm Ϫ1 agree with the experimental values 1125 and 1080 cm Ϫ1 , respectively. 2 Since diamond is effectively opaque for frequencies between 1600 and 2800 cm Ϫ1 and the intensity at frequencies above 2800 cm Ϫ1 is considerably less than that below 1500 cm Ϫ1 , the frequency of the O-H stretching mode was not obtained in the experiment.…”
supporting
confidence: 57%
“…The fact that the total energy of the TS is lower than that of the reactant is true of the dissociative adsorption of a NH 3 molecule on a Si-Si dimer. 15 The vibrational frequency of the adsorbed ϪOH fragment was calculated, and the computed values 1135 and 1110 cm Ϫ1 agree with the experimental values 1125 and 1080 cm Ϫ1 , respectively. 2 Since diamond is effectively opaque for frequencies between 1600 and 2800 cm Ϫ1 and the intensity at frequencies above 2800 cm Ϫ1 is considerably less than that below 1500 cm Ϫ1 , the frequency of the O-H stretching mode was not obtained in the experiment.…”
supporting
confidence: 57%
“…A nine carbon cluster MP2-calculation on OH-terminated diamond (100) surfaces resulted in an adsorption energy of −3.3 eV per OH for a 100 % surface coverage. This value is somewhat higher compared to −4.1 eV found in this work [37]. Another DFT study for the diamond (111) surface has reported on OH adsorption energies of −4.2 (−4.0) eV for the 1 × 1 (and 2 × 1) reconstruction.…”
Section: Hydroxyl-adsorptionmentioning
confidence: 36%
“…Two different models were suggested for the bonding structure of the diamond (100)1 × 1:O surface 31: the so‐called ketone or top site model with one oxygen double bonded to each carbon surface atom, and the ether or bridge site model with oxygen atoms connecting adjacent surface carbon atoms. Ab initio calculations and molecular dynamics simulations performed by Skokov et al 32 indicate that the (100) surfaces containing hydroxyl and O‐bridge groups are energetically more favorable than surfaces containing O‐on‐top structures. Hydrogen bonds are found to form among chemisorbed oxygenated species and their formation lowers the adlayer energy.…”
Section: Resultsmentioning
confidence: 99%
“…During the last two decades, molecular and activated oxygen (AO) adsorption and desorption phenomena on bare, partially and fully hydrogenated diamond surfaces were investigated both experimentally 12–28 and theoretically 29–32. The majority of this work was performed onto well defined (111), (100), and (110) surfaces, while much less efforts were invested into more common polycrystalline diamond films.…”
Section: Introductionmentioning
confidence: 99%